Big data e comunicação organizacional: novas fontes de dados disponíveis para reforçar o relacionamento com os públicos de interesse e apoiar os objetivos estratégicos - BALDO, Wallace Chermont (2018)
The study will investigate the impacts of big data systems on organizational communication. The general objective is to demonstrate how new information technology systems can transform and assist the planning and deployment of strategies in organizational communication. The specific objectives are: identify the components of organizational communication and the impacts generated by the new technologies on them; map new technological tools to capture and analyze data and their possible applications in organizational communication; contribute to broadening the understanding of moral, legal and ethical issues raised by the capture, storage and use of data by big data systems from stakeholders of the organization; explore specific cases. It is an original scientific work, non-quantitative, and non-experimental, developed accordingly to the constructivist perspective. It is characterized as an exploratory, bibliographical, documental, and telematics-based research, given to observe, record and analyze facts regarding the possibilities of using information technology systems by organizational communication professionals – in search of a broader view of the subject, not very studied, yet. The conclusion is that big data systems have the potential to lead a paradigm shift in corporate communication, which will require qualified personnel to translate the identified insights and, at the same time, should discuss and formulate guidelines to avoid misuse of data.